Gender Cyber-deconstruction Sosok Nyai Roro Kidul dan Dewi Sri pada Karya Kei Imazu - Chairunisa; Dwi Ayu Setiowati (Visi Sosial Humaniora, 2026)
This article develops the concept of cyberdeconstruction gender to read the representation of two Javanese mythical figures  Nyai Roro Kidul and Dewi Sri  in Kei Imazu's contemporary installation work. This approach combines cyberfeminism, ecofeminism, and visual mythology studies to examine how Imazu's digital-analogue art deconstructs traditional dichotomies (nature/culture, feminine/object, local/global) and reconfigures gender subjects through hybrid media. The primary data consists of a visual analysis of Imazu's works exhibited in The Sea is Barely Wrinkled (MACAN Museum, 2025), combined with contemporary ethnographic literature and cultural studies. The results of the study reveal three processes: (1) symbolic recombination  the combination of agrarian and maritime attributes that challenges traditional gender essences; (2) mystical technogenesis  the use of digital materiality and installation-based presentation that blurs the boundaries between human and non-human; and (3) politicisation of public space  works that invite local narratives into global discourse, modifying the mythical authority of women. The article concludes that Imazu's practice functions as an aesthetic political strategy that deconstructs and recomposes mythical feminine identities in the digital media era  relevant to gender studies, contemporary art, and visual anthropology. Recommendations include detailed field studies of coastal community perceptions and further interdisciplinary studies on the transformation of myths in digital space.